From "best practice" to "best fit": A framework for designing and analyzing pluralistic agricultural advisory services worldwide - Birner, Regina; Davis, Kristin E.; Pender, John L.; Nkonya, Ephraim M.; Anandajayasekeram, Ponniah; Ekboir, Javier; Mbabu, Adiel; Spielman, David J.; Horna, Daniela; Benin, Samuel; Cohen, Marc J. (International Food Policy Research Institute, 2006)
The paper develops a framework for the design and analysis of pluralistic agricultural advisory services and reviews research methods from different disciplines that can be used when applying the framework. Agricultural advisory services are defined in the paper as the entire set of organizations that support and facilitate people engaged in agricultural production to solve problems and to obtain information, skills and technologies to improve their livelihoods and well-being... To classify pluralistic agricultural advisory services, the paper distinguishes between organizations from the public, the private and the third sector that can be involved in (a) providing and (b) financing of agricultural advisory services. The framework for analyzing pluralistic agricultural advisory services presented in the paper addresses the need for analytical approaches that help policy-makers to identify those reform options that best fit country-specific frame conditions. Thus, the paper supports a shift from a “one-size-fits-all” to a “best fit” approach in the reform of public services... Based on a review of the literature, the paper presents a variety of quantitative and qualitative methodological approaches derived from different disciplines that can be applied when using the framework in empirical research projects. The disciplines include agricultural and institutional economics, communication theory, adult education, and public administration and management. The paper intends to inform researchers as well as practitioners, policy-makers and development partners who are interested in supporting evidence-based reform of agricultural advisory services.